Test of Transmission Error and Analysis of Dynamic Performance of a High Speed Straight Bevel Gear - Chen Qinglan; Jiang Ping; Hu Zehua; Tang Jinyuan (Jixie chuandong, 2016)
The dynamic transmission error of a straight bevel gear pair is tested and the relationship between the dynamic transmission error and the gear vibration is analyzed,with a straight bevel gear transmission system as the research object. The dynamic transmission error test system for the high speed straight bevel gear pair is developed and the transmission error curves are obtained. The dynamic property parameters of the gear pair are researched by the analysis of the experiment data with the signal processing approach. According to the comparison of the dynamic transmission error and the vibration behavior tested near the corresponding area of the gearbox,the results show,for the straight bevel gear pair,the shaft frequency components are the main frequency components of the dynamic transmission error,the low frequency components of the dynamic transmission error vary obviously with the rotation speed,the effect of the dynamic transmission error and the vibration acceleration near the supporting bearings on describing the dynamic responses are consistent.